Analisis Kepuasan Kerja Karyawan di Harris Resort Barelang Batam - Fedrya, Nurul Qurrota Aini; Surenda, Rian; Andres, Fran Serano (Departemen Pariwisata Universitas Negeri Padang, 2024)
Written based on the results of pre-research on employees at Harris Resort Barelang Batam on the job satisfaction they get and the purpose of this research is to analyze the job satisfaction of employees at Haris Resort Barelang Batam. Data collection techniques by distributing questionnaires. Quantitative descriptive research with clausal associative method. The population is Pruposive Sampling technique with primary data, job satisfaction at Harris Resort Barelang Batam was in the unfavorable category, amounting to 46.4%, in the range of scores 64-<75.